2017
DOI: 10.3389/fpsyg.2017.01635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Syllable-Based Reading Intervention in Poor-Reading Fourth Graders

Abstract: In transparent orthographies, persistent reading fluency difficulties are a major cause of poor reading skills in primary school. The purpose of the present study was to investigate effects of a syllable-based reading intervention on word reading fluency and reading comprehension among German-speaking poor readers in Grade 4. The 16-session intervention was based on analyzing the syllabic structure of words to strengthen the mental representations of syllables and words that consist of these syllables. The tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Therapies to improve the reading performance of dyslexics include therapies based on the discrimination of auditory stimuli [ 5 , 6 , 7 , 8 , 9 , 10 ], Phonological Awareness which comprises different approaches that are intended to promote reading skills [ 11 ], decomposing words into syllables and sounds [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], identifying phonems in words [ 19 , 20 , 21 ], naming letters, objects, numbers and colors [ 15 , 22 ], and rhyming [ 23 ]. Other therapies are based on visual movement discrimination training [ 24 , 25 , 26 , 27 , 28 ], a training to improve eye movement control [ 29 , 30 , 31 , 32 ], and syllable segmentation [ 33 , 34 , 35 , 36 ]. Therapy studies focused on breaking up words into syllables improved reading performance in children.…”
Section: Introductionmentioning
confidence: 99%
“…Therapies to improve the reading performance of dyslexics include therapies based on the discrimination of auditory stimuli [ 5 , 6 , 7 , 8 , 9 , 10 ], Phonological Awareness which comprises different approaches that are intended to promote reading skills [ 11 ], decomposing words into syllables and sounds [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], identifying phonems in words [ 19 , 20 , 21 ], naming letters, objects, numbers and colors [ 15 , 22 ], and rhyming [ 23 ]. Other therapies are based on visual movement discrimination training [ 24 , 25 , 26 , 27 , 28 ], a training to improve eye movement control [ 29 , 30 , 31 , 32 ], and syllable segmentation [ 33 , 34 , 35 , 36 ]. Therapy studies focused on breaking up words into syllables improved reading performance in children.…”
Section: Introductionmentioning
confidence: 99%
“…The second approach— repeated reading —refers to repetitive reading of sublexical items (e.g., syllables), words, sentences, or texts. Although some studies have shown positive effects on students' word reading fluency from repeated reading intervention (e.g., Müller, Richter, Karageorgos, Krawietz, & Ennemoser, 2017), several intervention studies from shallow orthographies have shown that the effects tend to be item‐specific and do not produce improvements in general reading fluency (Berends & Reitsma, 2007; Heikkilä, Aro, Närhi, Westerholm, & Ahonen, 2013; Hintikka, Landerl, Aro, & Lyytinen, 2008; Marinus, de Jong, & van der Leij, 2012; Thaler, Ebner, Wimmer, & Landerl, 2004). Thus, the development of effective evidence‐based methods to promote children's reading fluency is still in progress.…”
Section: Introductionmentioning
confidence: 99%
“…The authors asserted that those findings challenged the theory that phonological deficits alone cause reading impairment, since it was only when PA was trained in orthography that the impact on reading was significant. Similarly, Müller, Richter, Karageorgos, Krawietz, & Ennemoser (2017) examined a syllable-based word recognition intervention for German fourth graders with reading difficulties. Basic word reading skills were administered followed by testing the effects of this training on the efficiency of written word recognition and the potential transfer effects on reading comprehension skills at the text level.…”
Section: Discussionmentioning
confidence: 99%